Synthesis, Characterization, and Environmental Applications of Cu-Ni-Doped Bismuth Molybdate - Kashaf Sehar; Muhammad Saeed; Maida Murtaza; Manzar Zahra; Amir Waseem (Nanomaterials and Nanotechnology)
Bismuthoxide-based catalysts gained attention for photocatalytic remediation of environmental pollutants owing to their low cost, feasibility, stability, small, and tunable band gap. In the present work, bismuth molybdate was modified via transition metal doping to achieve maximum catalytic efficiency. This aim was accomplished by synthesizing novel Cu2+ and Ni2+ codoped bismuth molybdate (CuNi/Bi2MoO6, Cu/Bi2MoO6, and Ni/Bi2MoO6) which were utilized for heavy metal reduction and dyes degradation. Pure bismuth molybdate was also fabricated for comparative studies. All the prepared samples were characterized by XRD, Raman spectroscopy, SEM, and EDX. Optical studies for band gap calculations were carried out by UV-Visible spectrophotometry and decrease in band gap was observed in doped materials. Pseudo-first-order kinetic studies were performed to find the rate constants and regression values for Cr(VI) reduction and degradation of rhodamine B and malachite green using CuNi/Bi2MoO6. Codoped bismuth molybdate exhibited more than 95% photocatalytic performance for Cr(VI) reduction and degradation of rhodamine B and malachite green dyes. Reusability of catalyst was confirmed up to six cycles. Considering its catalytic proficiency, CuNi/Bi2MoO6 is anticipated to be utilized for more environment friendly applications in future.